Capturing pedestrian movement safety and security issues at major transportation interchanges - Bohari, Zulfadly Azizi; Bachok, Syahriah; Mohamed Osman, Mariana (International Journal of GEOMATE, 2013)
More often than not, transportation nodes such as stations, interchanges and terminals were designed without much consideration to the needs, ergonomics and behavior of prospective passengers and public transport users. This research reports the first phase of the validation of data for the capturing of pedestrian behaviours at major interchanges. Applying the methods of video recording and manual passenger counting, the study used a case study of Masjid Jamek public transport interchange in Kuala Lumpur, to record and validate the pedestrian access and egress movements. This research aims at analyzing these empirical data to estimate these movements to estimate and calibrate the more appropriate models for improving pedestrian flows at these interchanges. Public transport operators and authorities may use the models to plan and design these nodes more effectively and ensure safety and security of passengers and users, especially during peak hours and irregular influx of trip making during seasonal holidays or major events.